Strain rate dependent flow stress characterization using piezo-actuated micropress - Taureza, Muhammad (2015)
The effect of strain rate on the mechanical response during microforming deformation is investigated for commercially pure titanium and aluminum. Piezoelectric actuated micropress is used to generate controlled constant strain rate between 0.1 and 10 sec-1 in a compression experiment using three different sizes of specimens. Investigations suggest that the increase of free and constrained surface grains results in hardening-softening competition with miniaturization. In addition, loading rate in micro compression significantly influence the work hardening behavior for both materials.